DEVELOPMENT OF ALTERNATIVE TOURISM IN LAMPUNG IN AN EFFORT TO INCREASE INVESTMENT - Sanjaya, Deny; Nurdin, Nurliah; Utomo, Tri Widodo; Gedeona, Hendrikus Tri (President University, 2024)
The purpose of this study, among others, is to analyse the Whole of Government in the development of investment in the tourism sector of Metro city, as well as in efforts to increase investment and development model of investment in the tourism sector of Metro city. The method in analyzing the data of this research uses descriptive qualitative and data collection techniques with interviews, literature reviews, document reviews, and field surveys so that it is rich in information in data collection. The results showed that Metro City has considerable potential in the tourism sector, so that the condition of the destination needs to be improved continuously and attractive promotion for tourists. In addition to the lack of competent human resources, as well as the whole of government that is still partial. There are four types of tourist destinations, in an effort to increase investment in the tourism sector, public service malls are a necessity for investors. The conclusion in this study is that the whole of government needs to be implemented by every OPD in the Metro City government, with the design of the tourism sector investment development model as an alternative input to overcome problems more comprehensively.